2021
DOI: 10.3390/jcm10081690
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Peptides as Potential Non-Invasive Biomarkers for Lupus Nephritis: Results of the Peptidu-LUP Study

Abstract: Background: Lupus nephritis (LN) is a severe manifestation of Systemic Lupus Erythematosus (SLE). The therapeutic strategy relies on kidney biopsy (KB) results. We tested whether urinary peptidome analysis could non-invasively differentiate active from non-active LN. Design: Urinary samples were collected from 93 patients (55 with active LN and 38 with non-active LN), forming a discovery (n = 42) and an independent validation (n = 51) cohort. Clinical characteristics were collected at inclusion and prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…Detection and identification of particular peptides in complex biomatrices is of great importance also in peptidomic and proteomic analyses of biological fluids (blood, serum, plasma, CSF, urine, saliva). It can result in the discovery of new specific peptide biomarkers applicable in diagnosis, therapy, and prognosis of some diseases, for example, various kidney diseases [3], Covid-19 [4], Alzheimer's disease [5], and lupus nephritis (LN) disease [6].…”
Section: Determination In Biomatricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Detection and identification of particular peptides in complex biomatrices is of great importance also in peptidomic and proteomic analyses of biological fluids (blood, serum, plasma, CSF, urine, saliva). It can result in the discovery of new specific peptide biomarkers applicable in diagnosis, therapy, and prognosis of some diseases, for example, various kidney diseases [3], Covid-19 [4], Alzheimer's disease [5], and lupus nephritis (LN) disease [6].…”
Section: Determination In Biomatricesmentioning
confidence: 99%
“…In another CE-MS study, a marker model of 83 urinary peptides achieved the performance for diagnosis of periprosthetic joint infection with a sensitivity of 95%, a specificity of 90%, and an AUC of 0.96 [223]. On the other hand, CE-MS analyses of urinary peptidome of 55 patients with active LN and 38 patients with nonactive LN have shown that urinary peptides cannot discriminate between active and nonactive LN or predict early response to therapy [6].…”
Section: Determination In Biomatricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles describing the connection between urine composition and diseases using the data from the CE‐MS were recently reported. Valuable data were obtained for phenylketonuria [ 77 ], rheumatoid arthritis [ 78 ], systematic lupus erythematosus [ 79 , 80 ], chronic obstructive pulmonary disease [ 81 ], chronic graft‐versus‐host disease [ 82 ], liver fibrosis [ 83 ], and periprosthetic joint infection [ 84 ]. Besides the study of various diseases, this technique allowed the generation of the biomarker classifier of mice aging applicable to humans [ 85 ], the prediction of 1‐year mortality after discharge from the intensive care [ 86 ], and rapid screening of biomarkers indicating recent smoke exposure [ 87 ].…”
Section: Ce‐ms As a Tool For Metabolomic Studiesmentioning
confidence: 99%
“…1,2 In clinical medicine research, biomarkers are powerful tools to diagnose diseases, discover drugs, and monitor the treatment status of patients. 3 Because of the value of biomarkers in diagnosis, treatment, and detection, the discovery of biomarkers has been a great concern in clinical research. 4 It led to the upsurge of using "omics" technology to study biomarkers, especially proteomics.…”
Section: Introductionmentioning
confidence: 99%